Potential Clinical Role of Telomere Length in Human Glioblastoma - La Torre, D. (Università di Salerno, 2011)
Glioblastoma Multiforme (GBM) is the most common and lethal of human primary central nervous system (CNS) tumors. Due to the tumour’s intrinsic clinical and molecular heterogeneity, choice of initial treatment, prediction of survival, stratification of patients, prediction and monitoring of response to therapy, represent some of the greatest challenges in the management of GBM patients. Patients, despite optimal surgery, radiation and chemotherapy, still have a median survival of 14–16 months. A reason for this dismal prognosis is because of the relative inaccuracy of current prognostic markers, so far based on clinical or pathological variables. Molecular markers that effectively predict response to therapy and survival outcomes are limited. Consequently, there is a strong need to develop novel and independent markers of prognosis. Ideal biomarkers for solid tumors would serve one or more important functions. Telomeres, guanine-rich tandem DNA repeats of the chromosomal end, provide chromosomal stability, regulates important cellular processes, and seem to be implicated in human carcinogenesis. Recently, telomeres have been shown either to be associated with clinical markers of disease progression or to be independent markers of cancer prognosis in solid tumours, including GBM. Nevertheless, a corresponding comprehensive discussion of these promising developments in brain tumours has not yet been available in the literature. Therefore, here we reviewed studies focused on the assessment of telomeric length in brain tumours with the aim to emphasized those findings indicating a potential clinical role of telomeres in GBM. With the aim to enhance the awareness of the potential clinical role of telomeres’ length information in GBM, using a southern blot analysis, telomeric length in excised tumour samples was analyzed. Moreover, an attempt to correlated telomere length with patients’ overall survival, was also performed. The findings here reviewed shows some contradictory results, due to different tissues used as controls, but mainly to cellular and molecular heterogeneity in GBMs that drive molecular mechanisms controlling telomere length, included telomerase and Alternative Lengthening of Telomeres (ALT), through multiple mechanisms. However, overall these studies, including our own, are consistent with the hypothesis that GBMs’ telomeres were always shorter when compared with Normal Brain Tissue (NBT), and together with higher telomerase activity seem to be associated with malignancy and poor outcome; while tumours with ALT phenotype have longer telomeres, “less malignant” behaviour and better prognosis. We conclude that, although not entirely consistent in the type of telomere alteration, i.e., attrition vs. elongation, and unclear on the underlying mechanisms, multiple studies in brain tumours have shown that telomere dysfunctions are associated with parameters of clinical outcome in patients with GBMs and therefore will be part of novel risk assessment and prognostic modalities for patients with these still dismal disease.